2021
DOI: 10.1186/s12917-021-03069-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in metabolic and hormonal profiles during transition period in dairy cattle – the role of spexin

Abstract: Background This study aimed to evaluate spexin as a novel blood marker and to describe the relationship of this peptide with selected biochemical metabolites measured during the transition period in dairy cows. Additionally, mRNA expression of the spexin gene as well as spexin receptors – galanin receptor type 2 and galanin receptor type 3, was investigated in several bovine tissues. Blood samples were collected at weekly intervals starting at 21 days before the estimated parturition day until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 59 publications
(73 reference statements)
6
6
1
Order By: Relevance
“…[14] referred to the possible relation of GHRL gene with insulin level and food intake in cows. The results also similar with those of [15] who referred to the crucial role of GHRL gene in metabolic and hormones changes in dairy cattle. In conclusion, the current results showed a good relationship among milk traits and GHRL polymorphism especially in promoter site and the allele type which resulted from single nucleotide change from guanine to adenine make a wide variation among the individuals therefore, we can use the GHRL gene as a genetic marker for indirect selection to improve the milk production performance.…”
Section: Resultssupporting
confidence: 89%
“…[14] referred to the possible relation of GHRL gene with insulin level and food intake in cows. The results also similar with those of [15] who referred to the crucial role of GHRL gene in metabolic and hormones changes in dairy cattle. In conclusion, the current results showed a good relationship among milk traits and GHRL polymorphism especially in promoter site and the allele type which resulted from single nucleotide change from guanine to adenine make a wide variation among the individuals therefore, we can use the GHRL gene as a genetic marker for indirect selection to improve the milk production performance.…”
Section: Resultssupporting
confidence: 89%
“…In our study, there was a decrease in triglyceride and cholesterol concentrations in cows just before and after parturition. Similar observations have been made by other authors [30,31]. The reduced mean value of triglyceride concentration in the postpartum period compared with the prepartum period may be explained by the uptake of triglycerides by the mammary gland for milk fat synthesis during lactation [30].…”
Section: Discussionsupporting
confidence: 89%
“…Damage to hepatocytes in cows may be indicated by an increase in the activity of enzymes such as aspartate aminotransferase or gamma-glutamyl transferase in the serum [29,30]. In the studies conducted, no significant differences in AST and GGT activity were observed between the groups or in cows before and after calving.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, the exploration of this neuropeptide in domestic cattle is notably limited. Research by Mikuła et al [29] previously delved into the role of SPX and other associated metabolites during the transition period in dairy cows. Primarily, this inquiry focused on identifying SPX's potential as a novel blood marker, offering insights into the health status of animals, particularly during transitional phases.…”
Section: Discussionmentioning
confidence: 99%